PELAKSANAAN LAYANAN BIMBINGAN KONSELING BAGI ANAK BERKEBUTUHAN KHUSUS - Elviana Elviana (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2019)
This research is conducted to find out how the counseling process is done to guide students with special needs and what problems the teacher-counselors encounter in counseling services to help the students of the inclusive schools (SMPN) 1 Kabupaten Bireuen. This is qualitative-descriptive research which used interview and observation to gain data needed. The results of the study showed that there were no specific counseling services at the schools. Consequently, counseling for the students (ABK) has not worked well. Besides, in giving counseling services to the students, the teachers-counselors did not arrange or planned specific counseling services and did not have a manual guide to lead the services. If students needed help or had problems, the counselors just took them to their rooms and gave some advice without any further treatments. And there were no assisstantance-teachers who helped the students whenever they needed. The problems faced by the teacher-counselor was that most of them were not real counselors but teachers with an additional job who had less knowledge of the issues especially in treating students with special needs. Additionally, the socialization and training for the counselor to develop their knowledge were not available while the parents of the students were not able to manage them. The other problem was the students themselves could not adapt easily in their school environment.